Design of compact multi-mode microstrip resonator filters for dual-band application - Nurshamimi Rosli; Siti Aminah Md Akhir; Siti Zuraidah Ibrahim; Nur Baya Mohd Hashim; Nurehansafwanah Khalid (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents the design of compact multi-mode microstrip resonator filters for dual-band application. The design is simulated using Advanced Design System (ADS) 2016 software. The benefit of the proposed filter is found to have a dual-mode frequency, where the odd-mode resonant frequency is the fundamental frequency represented by the length of the resonator while the even-mode resonant frequency is represented by the length of the stub. To validate the design, a prototype is fabricated on Rogers RO4003C substrate and measured using PNA Network Analyzer.